Rituximab in diffuse cutaneous systemic sclerosis: an open-label clinical and histopathological study. Issue 01 (22nd December 2008) - Smith, V; Van Praet, J T; Vandooren, B; Van der Cruyssen, B; Naeyaert, J-M; Decuman, S; Elewaut, D; De Keyser, F
Abstract : Objectives: The safety and potential efficacy of rituximab was examined in diffuse cutaneous systemic sclerosis (dc-SSc). Methods: A 24 week open-label study in which eight patients with dc-SSc received an infusion of 1000 mg rituximab administered at baseline and day 15, together with 100 mg methylprednisolone at each infusion. Assessment included CD19+ peripheral blood lymphocyte number, skin sclerosis score, indices of internal organ functioning, the health assessment questionnaire disability index, the 36-item Short Form health survey and histopathological evaluation of the skin. Results: Ritixumab induced effective B-cell depletion in all patients (<5 CD19+ cells/μl blood). There was a significant change in skin score at week 24 (p<0.001). Also, significant improvements were measured in the dermal hyalinised collagen content (p = 0.014) and dermal myofibroblast numbers (p = 0.011). Two serious adverse events occurred, which were thought to be unrelated to the rituximab treatment. Conclusions: Rituximab appears to be well tolerated and may have potential efficacy for skin disease in dc-SSc. This study is registered with ClinicalTrials.gov, number NCT00379431.